Pilot-scale evaluation of bioremediation efficiency by powder formulation of a consortium of hydrocarbon-degrading bacteria - Ali Abolhasani Soorki; Mahnaz Mazaheri Assadi; Seyed Omid Ranaei Siadat (علوم محیطی, 2019)
Introduction: Oil pollution can cause serious and long-term damage to the environment and the health of human communities. Hydrocarbon compounds can remain in nature for a long period and become environmental pollutants. The elimination of hydrocarbon contamination is still a challenge for researchers of different disciplines. Bioremediation is a branch of biotechnology that can be used to eliminate these contaminants. However, most findings on the evaluation of factors affecting oil bioremediation are obtained from laboratory studies, and research in this area is very limited in pilot or field scale studies. Studies show that bioremediation agents that are effective in vitro may be significantly less effective on a large scale because laboratory studies cannot always simulate the real world's conditions due to spatial heterogeneity, biological interactions, weather effects, and restrictions on access to mineral nutrients. In this study, the performance and effectiveness of a consortium of hydrocarbon-degrading bacteria were evaluated under natural conditions in a pilot scale. Material and methods: To conduct this research, a bacterial consortium of five strains of bacteria including Alcanivorax dieselolei, Thalassospira xianheensis, Rhodococcus ruber, Gracilibacillus dipsosauristrain and a Microbacterium sp. were proliferated in a 500-liters semi-industrial fermenter. Then, the microbial cells were dried by the spray-drying method after sedimentation in the fermenter and formulated on the diatomaceous powder as a stabilizing bed. By blending this microbial powder with appropriate nutrient supplements, the final formulation of the oil-degrading microbial powder was produced. A field test was conducted to evaluate the performance of this microbial powder on crude oil contaminated soils in Kharg Island. For this purpose, soils contaminated by heavy crude oil resulting from oil pipeline leakage were examined for 14 days in two separate blocks, including a control block and a bioaugmentation block treated by the petroleum-degrading microbial powder. Reduction of total petroleum hydrocarbons concentration and soil temperature changes were measured during the test period. Results and discussion: The mean of TPH in the first day was 341 mg per gram soil. In the control block, the reduction of petroleum hydrocarbons after 14 days of the experiment was 14.2%, which could be due to the activity of the population of native soil bacteria or due to physico-chemical processes such as evaporation and photo-oxidation. In contrast, in the soil treated with the petroleum-degrading microbial powder, the concentration of hydrocarbons at the end of the test period was reduced by 70.6% to 99 mg per gram soil. These results indicate the very rapid performance of this microbial consortium in the decomposition of hydrocarbons. Also, due to the increased activity of bacteria and degradation of hydrocarbons, soil temperature was increased about 11 degrees Celsius in the block treated with microbial powder. Increasing the temperature of the soil as a result of the activity of bacteria, especially in cold regions or in the cold seasons, can lead to the further increase of soil microbial population’s metabolism and increase the biodegradation efficiency. This is especially important in the case of oil pollution in Polar regions. Conclusion: The results of this study showed that the use of a microbial consortium for the biological treatment of contaminated soils with very high concentrations of petroleum hydrocarbons, such as crude oil spill from oil pipelines, could be beneficial. Also, the use of powdered products is an effective solution due to the ease of operation and independency from complex and expensive equipment. In addition, due to the high level of early population of bacteria that can degrade the oil, the addition of a microbial consortium can increase the temperature of the soil and increase the activity of native soil populations.